APPLICATION OF FUZZY TSUKAMOTO METHOD IN DETERMINING THE STOCK OF COCONUT SHELL CRAFT GOODS - Esti Pratiwi, Yasinta; Saqila Istanti, Fishilia (CV. Fahr Publishing, 2024)
This research applies the Fuzzy Tsukamoto Method to optimize the inventory management of coconut shell handicraft products in Bantul Regency, Indonesia. The aim is to develop a predictive system to determine production quantities based on market demand and inventory levels, so as to overcome challenges such as over- and under-stocking. Data was collected from Marem.id's production records between January and April 2024, which included demand, inventory, and production variables. Fuzzy modeling is performed with three variables: two inputs (demand and inventory) and one output (production). The system integrates fuzzification, inference, and defuzzification processes to calculate the optimal production level. The results show that for April 2024, a production quantity of 92,432 units is recommended to meet demand and maintain efficient inventory levels. This approach improves operational efficiency, reduces costs, and increases competitiveness in local and international markets.